2022
DOI: 10.1084/jem.20220498
|View full text |Cite|
|
Sign up to set email alerts
|

Biallelic PAX5 mutations cause hypogammaglobulinemia, sensorimotor deficits, and autism spectrum disorder

Abstract: The genetic causes of primary antibody deficiencies and autism spectrum disorder (ASD) are largely unknown. Here, we report a patient with hypogammaglobulinemia and ASD who carries biallelic mutations in the transcription factor PAX5. A patient-specific Pax5 mutant mouse revealed an early B cell developmental block and impaired immune responses as the cause of hypogammaglobulinemia. Pax5 mutant mice displayed behavioral deficits in all ASD domains. The patient and the mouse model showed aberrant cerebellar fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“… AMutation of the Pax5‐binding sequence of PAIR4. The nucleotides of PAIR4, which match the Pax5 consensus recognition sequence (Kaiser et al , 2022), are underlined and were mutated to the nucleotides indicated in red (∆Pax5). BMutation of the CTCF‐binding sequence of PAIR4. The nucleotides of PAIR4, corresponding to the consensus CTCF‐binding motif (Hill et al , 2020), are underlined and were mutated to the nucleotides indicated in red (∆CTCF). C, DSchematic diagram of the Gfp ‐linked PAIR4‐V8.7E module with the Pax5‐ or CTCF‐binding site mutation, which was used for the generation of the Igh P4∆Pax5GV or Igh P4∆CtcfGV allele, respectively. E, GPax5 and CTCF binding to the wild‐type and mutant PAIR4 sequences.…”
Section: Resultsmentioning
confidence: 99%
“… AMutation of the Pax5‐binding sequence of PAIR4. The nucleotides of PAIR4, which match the Pax5 consensus recognition sequence (Kaiser et al , 2022), are underlined and were mutated to the nucleotides indicated in red (∆Pax5). BMutation of the CTCF‐binding sequence of PAIR4. The nucleotides of PAIR4, corresponding to the consensus CTCF‐binding motif (Hill et al , 2020), are underlined and were mutated to the nucleotides indicated in red (∆CTCF). C, DSchematic diagram of the Gfp ‐linked PAIR4‐V8.7E module with the Pax5‐ or CTCF‐binding site mutation, which was used for the generation of the Igh P4∆Pax5GV or Igh P4∆CtcfGV allele, respectively. E, GPax5 and CTCF binding to the wild‐type and mutant PAIR4 sequences.…”
Section: Resultsmentioning
confidence: 99%
“…PAX5. A single individual with compound heterozygous PAX5 variants had reduced levels of all serum Ig isotypes and peripheral B-lymphopenia ( Kaiser et al, 2022 ). Mice expressing patient-specific PAX5 alleles ( Pax5 R31Q/E242 * ) had an accumulation of pro-B cells and 5–10-fold fewer pre- and immature B cells in BM compared to WT mice ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Pax5 R31Q/E242 * mice also had significantly reduced peripheral B cells and levels of serum IgG (10–20-fold), IgA (∼5-fold), and IgM (2-fold). Mechanistically, Pax5 R31Q encoded a hypomorphic protein, impaired in regulating 10–20% of PAX5 target genes ( Kaiser et al, 2022 ). Thus, human PAX5 deficiency blocks B cell development resulting in B cell cytopenia, hypogammaglobulinemia, and impaired Ab responses.…”
Section: Introductionmentioning
confidence: 99%
“…Following up on the demonstration that the ErasmusLadder enables the differentiation between cerebellar mutants in cross sectional studies (Van Der Giessen et al, 2008; Renier et al, 2010; Schonewille et al, 2011; van der Vaart et al, 2011; Baudouin et al, 2012; Saab et al, 2012; Vinueza Veloz et al, 2012; Galliano et al, 2013; Marques et al, 2015; Vinueza Veloz et al, 2015; Ha et al, 2016; Peter et al, 2016; Rahmati et al, 2016; French et al, 2018; Prekop et al, 2018; Sathyanesan et al, 2018; Sayed-Zahid et al, 2019; Wu et al, 2019; Almeida et al, 2020; Grasselli et al, 2020; Haify et al, 2020; Namdar et al, 2020; Peter et al, 2020; Blot et al, 2021; Lang-Ouellette et al, 2021; Vacher et al, 2021; White et al, 2021; Kaiser et al, 2022; Klomp et al, 2022; Lauffer et al, 2022; Ottenhoff et al, 2022; Birkisdóttir et al, 2023a; Fang et al, 2023) (Table S1), in this study we aimed to probe the ErasmusLadder as a tool for quantifying disease onset and progression in cerebellar disease models. We examined two mouse lines displaying progressive Purkinje cell degeneration, and followed their behavioral performance from early to severe symptomatic stages.…”
Section: Introductionmentioning
confidence: 99%